Studi Literatur : Penyakit yang Dapat Dicegah dengan Imunisasi - Roma Rizky Siregar, Nabila; Nasution, Irfan Sazali; Aulia, Aisah Febri; Waini, Dinda Cahaya; Yolanda, Fauzia Afrida; Lestari, Feyza; Mawaddah Siregar, Sabrina Rizki; Raihanah, Vidya (Pustaka Galeri Mandiri, 2025)
Immunization is a preventive effort aimed at providing protection against infectious diseases through vaccination in children. Every child must receive complete immunizations to avoid serious illnesses that may lead to weakness, disability, and death. Although immunization programs have been widely implemented, several vaccine-preventable diseases (VPDs) are still found in Indonesia. This situation is influenced by uneven immunization coverage, population mobility, sociocultural factors, and increasing public skepticism toward vaccines. This study aims to analyze the mechanisms of transmission and preventive measures for diseases that can be prevented through immunization, including Hepatitis B, Tuberculosis, Measles, Polio, Diphtheria, and PertussisThis study employed a literature review method by collecting references from books and scientific articles obtained through Google Scholar and PubMed databases. The inclusion criteria consisted of relevant topics, full-text availability, and accessible sources. The review shows that OPV and IPV vaccination is effective in preventing polio. Routine immunization and improved sanitation play an essential role in preventing diphtheria, pertussis, and other infectious diseases. Furthermore, community education and the active involvement of health workers significantly contribute to the success of immunization programs. Successful control and prevention of infectious diseases in Indonesia rely heavily on equitable immunization coverage, continuous public education, and strengthening of the health system. Collaborative efforts between the government, health workers, and the community are crucial to addressing existing challenges and ensuring that immunization programs achieve their targets in reducing incidence, complications, and mortality from vaccine-preventable diseases.